Basics of blood management - Seeber, Petra; Shander, Aryeh (Hoboken : John Wiley & Sons, 2012)
To reduce transfusion-related morbidity and mortality, it is recommended that an integrated approach to blood management is employed using all available tools to reduce a patient's exposure to donor blood. Meeting the need for a book covering the concepts of blood management as a trend towards multidisciplinary blood management, this new edition is an important resource, providing healthcare professionals with a tool to develop background knowledge in blood management, its organization, methods and tools. Practicing clinicians will be fully prepared to successfully start and run blood manageme.
17: Blood-Derived Pharmaceuticals18: Transfusion Medicine; 19: Step by Step to an Organized Blood Management Program; 20: Law, Ethics, Religion, and Blood Management; Appendix A: Detailed Information; Appendix B: Sources of Information for Blood Management; Appendix C: Program Tools and Forms; Appendix D: Teaching Aids: Research and Projects; Index.
Print version record.
Keywords: Transfusion-free surgery; Blood -- Transfusion; Blood banks; Blood -- Transfusion; Social Science; Medicine; Health; MEDICAL -- Allied Health Services -- General; Blood banks; Blood -- Transfusion; Transfusion-free surgery; Electronic books